Mathematical modeling of chemical reactions in microreactors - Мірошниченко, Юлія Анатоліївна; Безносик, Юрій Олександрович; Бондаренко, Олена Сергіївна (Technology audit and production reserves, 2015)
In this paper it is conducted a review of published data on the use of microstructural reactors for the optimization of chemical processes and reactions, a detailed description of which is possible with the use of modern methods and modeling tools. Microreactor is a miniature reactor apparatus having dimensions in the submillimeter range. Chemical reactions in the microreactor are carried out in one or a plurality of parallel channels, the channel diameter is not more than the mean free path of the molecules in the gas phase reactions. The advantages of the microreactors may include a large surface area contact between the phases, laminar flow (and reducing energy costs and increasing residence time), high radial diffusion coefficient, simplifying scaling and enhanced characteristics of safety selectivity of processes occurring in them. On the basis of established technical and economic advantages of microsystem devices it is proved the feasibility of their implementation in production.